2009
DOI: 10.1503/cmaj.080456
|View full text |Cite
|
Sign up to set email alerts
|

Acute allergic interstitial nephritis after use of pantoprazole

Abstract: The case: A 57-year-old man presented to hospital with a 2-week history of progressive malaise, myalgia, fever, nausea, vomiting, diarrhea, polyuria and polydipsia. He had a history of gastresophageal reflux that did not respond to ranitidine. He had started taking oral pantoprazole (40 mg daily) 6 weeks earlier. The patient had a history of coronary artery disease and was taking acetylsalicylic acid (81 mg daily) and atorvastatin (40 mg daily). He reported having taken ibuprofen (400 mg) for myalgia no more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“… 10 A unique case report also suggested that a 57-year-old male in Britain, suffering from gastroesophageal reflux, was unresponsive to ranitidine and was therefore prescribed pantoprazole, which resulted in acute interstitial nephritis. 11 …”
Section: Discussionmentioning
confidence: 99%
“… 10 A unique case report also suggested that a 57-year-old male in Britain, suffering from gastroesophageal reflux, was unresponsive to ranitidine and was therefore prescribed pantoprazole, which resulted in acute interstitial nephritis. 11 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore he was prescribed pantoprazole that developed acute interstitial nephritis. 12 The other drugs that were prescribed to the patient in the present study include Ceftriaxone, a third-generation antibiotic, known to have various adverse effects. A study in this hospital conducted on 2014 showed 33.4% of the ADRs are caused by this antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…Microscopic hematuria is present in up to 90% of the cases, but hypertension and edema are not characteristic features. 27 Rather, children present with symptoms suggesting an inability to concentrate urine, such as polyuria or new-onset enuresis. The inability to concentrate the urine is secondary to inflammation in the renal medulla, with loss of tubular function, especially water reabsorption.…”
Section: Nephrological Causes Of Hematuriamentioning
confidence: 99%